ANALISA SUPPLY DAN DEMAND BETON READYMIX DI KOTA MALANG - Angga Saputra Dwi Wardhana, Suhariyanto, Sugeng Riyanto (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2015)
As civil constructions are growing rapidly in Malang, readymix concrete is in a great demand. The writer intends to find out the capacity of average readymix supply of 4 different companies, the capacity of average readymix demand of some construction projects in Malang, and some influential problems of both readymix supply and demand. This thesis includes a qualitative descriptive study. Questionnaires were distributed to some users and producers of readymix concrete in Malang.The questionnaires result is average 117.5 m3/day capacity of readymix supply in normal production and average 200 m3/day capacity of readymix supply in peak production, average 92 m3/day capacity of readymix demand large scale users, average 45 m3/day capacity of readymix demand medium scale users, average 17 m3/day capacity of readymix demand small scale users, and some problems of less material to make readymix concrete and less concrete mixer truck unit to service users.Keywords: demand, producer, readymix concrete, supply, user